Host Adaptation and the Alteration of Viral Properties of the First Influenza A/H1N1pdm09 Virus Isolated in Japan - Ainai, Akira; Hasegawa, Hideki; Obuchi, Masatsugu; Odagiri, Takato; Ujike, Makoto; Shirakura, Masayuki; Nobusawa, Eri; Tashiro, Masato; Asanuma, Hideki (PloS one, 2015)
A/Narita/1/2009 (A/N) was the first H1N1 virus from the 2009 pandemic (H1pdm) to be isolated in Japan. To better understand and predict the possible development of this virus strain, the effect of passaging A/N was investigated in Madin-Darby canine kidney cells, chicken eggs and mice. A/N that had been continuously passaged in cells, eggs, or mice obtained the ability to grow efficiently in each host. Moreover, A/N grown in mice had both a high level of pathogenicity in mice and an increased growth rate in cells and eggs. Changes in growth and pathogenicity were accompanied by amino acid substitutions in viral hemagglutinin (HA) and PB2. In addition, the adapted viruses exhibited a reduced ability to react with ferret antisera against A/N. In conclusion, prolonged passaging allowed influenza A/N to adapt to different hosts, as indicated by a high increase in proliferative capacity that was accompanied by an antigenic alteration leading to amino acid substitutions.